1995
DOI: 10.1104/pp.109.3.1047
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutathione Reductase but Not Glutathione Synthetase Leads to Increases in Antioxidant Capacity and Resistance to Photoinhibition in Poplar Trees

Abstract: A poplar hybrid, Populus tremula x Populus alba, was transformed with the bacterial genes for either glutathione reductase (CR) (gor) or glutathione synthetase (CS) (gshln. When thegorgene was targeted to the chloroplasts, leaf CR activities were up to 1000 times greater than in all other lines. In contrast, targeting to the cytosol resulted in 2 to 10 times the CR activity. CR mRNA, protein, and activity levels suggest that bacterial CR is more stable in the chloroplast. When the gshll gene was expressed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
226
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(262 citation statements)
references
References 34 publications
26
226
0
1
Order By: Relevance
“…We found that elevation of plastid GR activity over-rides feedback control of glutathione synthesis leading to elevated total glutathione levels. Broadbent et al (1995) and Foyer et al (1995) report a similar finding in nuclear transformants of tobacco and poplar respectively.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We found that elevation of plastid GR activity over-rides feedback control of glutathione synthesis leading to elevated total glutathione levels. Broadbent et al (1995) and Foyer et al (1995) report a similar finding in nuclear transformants of tobacco and poplar respectively.…”
Section: Discussionsupporting
confidence: 62%
“…However, our finding matches that of Creissen et al (1999) who increased GSH levels by transformation with a gene for a chloroplast-targeted c-glutamylcysteine synthetase (c-ECS) and found increased oxidative stress, which they explained on the basis of impaired redox sensing in the chloroplast. We contend that the increased MV sensitivity of the transplastomic lines over-expressing GR has a similar basis, although it is not reflected in a study in poplar (Foyer et al 1995) in which chloroplast targeted GR did result in improved oxidative stress tolerance. Another study with tobacco (Broadbent et al 1995) showed considerable interline variation, some GR over-expressing lines giving a modest increase in oxidative stress tolerance, while others did not.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several genes encoding for plant antioxidant enzymes have been cloned, characterized, and used in the construction of transgenic lines. Transgenic plants overexpressing SOD (Bowler et al, 1991;Van Camp et al, 1996;Breusegem et al, 1999;Alscher et al, 2002;Feki et al, 2016), APX (Wang et al, 1999), GR (Foyer et al, 1995), GPX (Roxas et al, 1997(Roxas et al, , 2000 and CAT (Feki et al, 2015) showed tolerance to various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of SOD and CAT as an adaptive response to oxidative stress has been reviewed (Mittler, 2002). In addition, effective resistance to prolonged stress would necessitate an augmented capacity for ascorbate regeneration, a process at least partly dependent on the tripeptide thiol (glutathione) in higher plants (Foyer et al, 1995). An important role in glutathione oxidation to glutathione disulfate is played by the latter enzyme in the ascorbate-glutathione cycle, glutathione reductase (GR).…”
Section: Introductionmentioning
confidence: 99%